STUDY THE ACTIVITY OF TITANIUM DIOXIDE NANOPARTICLE USING ORANGE G DYE - Algubury, Hazim Y. (Malaysian Journal of Science, 2016)
In this article photocatalytic degradation of orange G dye was carried out using titanium dioxide nanoparticles under UV irradiation. The amount of photocatalyst, concentration of orange G dye, effect of light intensity and effect of PH were studied as variables. The highest photocatalytic degradation of orange G dye was observed at 0.14 gm/100cm3 of titanium dioxide nanoparticles and 15ppm of dye. Orange G dye photocatalytic degradation was favorable in the PH 6.4 and 8.22 mW/cm2 light intensity. Photocatalytic degradation of orange G dye follow the first order of reaction .photocatalytic degradation of orange G dye has been studied using different concentrations of titanium dioxide nanoparticles suspended in an aqueous solution of orange G dye irradiated by 125 watts ultraviolet radiation in a vessel reactor at room temperature, with 10 cm3/min air bubble has been passed through the solution .Photocatalytic degradation of orange G dye presence of light and catalyst is essential for the degradation. Increasing dye concentration resulted in decreased photocatalytic degradation efficiency. The percentage efficiency of degradation reactive blue equals 93.98 % .The activation energy has been calculated it was found equal to 22.29 Â±1 kJ.mol-1. All experiments are determined using UV-visible spectrophotometer analyser. KEYWORDS: Photodegradation, Nanoparticle, Orange G, Titanium dioxide.